Analysis of Social Support Role Systems in the Long-Term Outcomes of Ponseti-Treated Clubfoot Patients at RSUP H. Adam Malik Medan - Nico Sutanto; Otman Siregar; Iman Dwi Winanto (Universitas Muhammadiyah Palu, 2025)
Congenital talipes equinovarus (clubfoot), if left untreated, can result in significant physical disability. While the Ponseti method has demonstrated high efficacy as a primary treatment modality, its long-term success depends substantially on consistent postoperative management and brace compliance, factors potentially influenced by social support systems. This study examines the impact of social support structures on treatment outcomes in clubfoot patients managed with the Ponseti technique at a tertiary referral center. We conducted a cross-sectional analytical study involving 80 pediatric clubfoot cases (mean age: 29.05±35.11 months; male predominance: 57.5%). Through structured interviews and retrospective medical record review, we evaluated multiple dimensions of social support (family engagement, community resources, healthcare accessibility) and their correlation with long-term therapeutic outcomes (recurrence rates, bracing adherence, functional assessments). Statistical analysis employed chi-square tests and multivariate logistic regression models. Our findings revealed significant associations between robust family support systems (p=0.015) and community-based assistance programs (p=0.032) with favorable long-term outcomes. Multivariate analysis identified consistent primary caregiver involvement (p=0.008; prevalence ratio [PR]=4.12) and access to rehabilitation services (p=0.022; PR=2.89) as independent predictors of treatment success. Socioeconomic indicators showed no statistically significant correlation. These results underscore the critical role of multidimensional social support in optimizing Ponseti method outcomes. We recommend integrating family education initiatives and community support networks into standard clubfoot management protocols. Further multicenter prospective studies are warranted to validate these findings across diverse sociocultural contexts.